Faktor – Faktor Yang Berhubungan Dengan Kejadian Diare Pada Bayi di Wilayah Kerja Puskesmas Sungsang Banyuasin II - Marta Indah , Lusi; Arsi , Ranida; Utama Saputra , Andre (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Diarrhea is a leading cause of death worldwide, accounting for 5–10 million deaths per year. The magnitude of this problem is evident in the high mortality rate due to diarrhea and morbidity, especially in children aged 6–12 months who are vulnerable groups. Diarrhea remains a global health problem, including in Indonesia. Many factors influence the incidence of diarrhea, such as maternal knowledge, maternal attitudes, exclusive breastfeeding, and handwashing behavior. The purpose of this study was to determine the factors associated with the incidence of diarrhea in toddlers in the working area of the Sungsang Banyuasin II Community Health Center. This study used an analytical survey design using a cross-sectional approach. The population in this study were all 76 mothers of infants at the Sungsang Community Health Center. The sample in this study was obtained using the Slovin formula of 30 people. The sampling technique was carried out using purposive sampling. Bivariate analysis used the chi-square test. The results of the study explained that there was a relationship between knowledge and the incidence of diarrhea in infants (p = 0.003). There was a relationship between attitudes and the incidence of diarrhea in infants (p = 0.000). There is a relationship between exclusive breastfeeding and the incidence of diarrhea in infants (p=0.004). There is a relationship between handwashing behavior and the incidence of diarrhea in infants (p=0.000). It is hoped that mothers will pay more attention to their babies’ health by increasing their knowledge about diarrhea.